Deteksi Kadar Keasaman Media Tanah Untuk Penanaman Kembali Secara Monitoring - Rufchotuz Zuhrotu Wardah (Jurnal Jaringan Telekomunikasi, 2019)
The development of the Indonesian agricultural sector until 2014 according to the Strategic Plan data of the Ministry of Agriculture for 2015–2019 is about 3.90% of the economic sector. One of the most important parameters for improvement efforts is soil. Soil quality on agricultural land is one important thing that needs special attention in its management. It is not easy to create ideal soil conditions for plants. For that, farmers need to know the variables that affect ideal conditions. The easiest way to find out the variable is to measure the pH and humidity of the soil conditions. Evaluation of soil fertility in chili plants is still done manually through visual observation. One of the factors that makes chili plants die before they bear fruit. In this research, a web monitoring system will be made on the planting medium of chilies based on soil acidity and soil moisture using sensors that can be monitored online. Data will be stored in the database and displayed on the web. The results obtained on the growing medium of chili plants produced soil suitable for chili plants, namely soil media sandy which has a moisture value of 7 to 8 and a pH value of 6.5-7.5. The average time needed to communicate between nodes to the website is 344 ms, which in the TIPHON standardization the average value of delay in sending data from the device to the website belongs to the 3rd index, which means that the process is of moderate quality.